EFFECTIVENESS OF THE KANGAROO METHOD AS A TREATMENT FOR LOW BIRTH WEIGHT BABY (LBWB) - Ifalahma , Darah; Setyorini, Catur; Zulfa Rosyidah, Muslihatun (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Low birth weight babies are a risk factor that contributes to infant deaths and births, especially during the perinatal period. The impact of the birth of low birth weight babies affects the quality of future generations, characterized by slow growth and development of children and will have an impact on decreasing intelligence. Conditions that occur in low birth weight babies are that the temperature regulation center is not optimal, brown fat and subcutaneous tissue are thin, inadequate muscle growth and organ immaturity. Conditions like this cause low birth weight babies to experience different physiological responses to babies with normal birth weight. The death of low birth weight babies can be prevented using interventions that are inexpensive, easy to carry out and effective, namely the kangaroo method of care. The kangaroo method is a method of caring for newborns by placing the baby between the mother's breasts so that there is direct contact between the mother's skin and the baby's skin. The kangaroo method of care is an alternative for caring for low birth weight babies so that mothers can easily breastfeed their babies more frequently and exclusively. The aim of the research is to review and recommend kangaroo treatment methods that have a positive impact and can reduce morbidity in low birth weight babies. The search method for relevant articles uses Google Scholar and Garuda databases. Search for articles using predetermined keywords and criteria. Using population, intervention, conclusion, and output (PICO) analysis. Conclusion: The kangaroo method is effective as a treatment for low birth weight babies. The positive effect of the kangaroo method on low birth weight babies is increasing the baby's body weight, maintaining the stability of the baby's physiological responses including increasing body temperature, heart rate frequency and oxygen saturation which are consistently within the normal range, and increasing the mother's confidence in caring for the baby.